2020
DOI: 10.3390/molecules25184122
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Regulates CPT1A to Promote β-Oxidation in HepG2 Cells

Abstract: Leucine-rich repeat kinase 2 (LRRK2) is involved in lipid metabolism; however, the role of LRRK2 in lipid metabolism to affect non-alcoholic fatty liver disease (NAFLD) is still unclear. In the mouse model of NAFLD induced by a high-fat diet, we observed that LRRK2 was decreased in livers. In HepG2 cells, exposure to palmitic acid (PA) down-regulated LRRK2. Overexpression and knockdown of LRRK2 in HepG2 cells were performed to further investigate the roles of LRRK2 in lipid metabolism. Our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Prolonged enhancement of CPT1A activity can lead to increased mitochondrial energy metabolism leading to heightened reactive oxygen species generation and causing cellular damage and apoptosis [60]. Whereas, a decrease in CPT1A expression can lead to reduced β-oxidation in liver and could contribute to fatty acid accumulation and inflammation in hepatocytes [61]. Thus, our study could show that the reduced levels of intracellular lipids in both the pretreated and concurrently treated HepG2 cells and primary rat hepatocytes with SKK were through the modulation of the FFA-stimulated steatosis related transcription factors (SREBP1c and C/EBPα), and associated lipogenic gene (FAS), which in turn also normalized the fatty acid transporter (CPT1A) gene expression levels responsible for the transport of fatty acids for mitochondrial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged enhancement of CPT1A activity can lead to increased mitochondrial energy metabolism leading to heightened reactive oxygen species generation and causing cellular damage and apoptosis [60]. Whereas, a decrease in CPT1A expression can lead to reduced β-oxidation in liver and could contribute to fatty acid accumulation and inflammation in hepatocytes [61]. Thus, our study could show that the reduced levels of intracellular lipids in both the pretreated and concurrently treated HepG2 cells and primary rat hepatocytes with SKK were through the modulation of the FFA-stimulated steatosis related transcription factors (SREBP1c and C/EBPα), and associated lipogenic gene (FAS), which in turn also normalized the fatty acid transporter (CPT1A) gene expression levels responsible for the transport of fatty acids for mitochondrial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…CPT1a-overexpressing mice were protected against obesity-induced weight gain, obesity-induced insulin resistance, and hepatic steatosis [ 29 , 30 ]. Despite the plethora of reports showing upregulation in cellular and animal models, the exact upstream events that lead to increased expression of CPT1a are unclear [ 31 ]. A recent report indicated that the expression of the gene is regulated by methylation and by binding of factors such as C/EBPbeta, PPARalpha, PGC1alpha, and BAF60a to the gene [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect on oxidation appears to be through LRRK2 regulation of the mitochondrial fatty acid transporter carnitine palmitoyltransferase 1A and the β-oxidation proteins peroxisome proliferator-activated receptor α and AMP-activated protein kinase. This suggests that LRRK2 plays a role in fatty acid catabolism [ 89 ]. In a recent untargeted lipidomics study of LRRK2 mutation carriers, serum lipids significantly discriminating LRRK2 G2019S mutation carriers from non-carriers belonged to pathways related to energy production, including mitochondrial oxidative phosphorylation (acylcarnitine, diacylglycerol and triacylglycerol species), glycerolipid metabolism (diacylglycerol, monogalactosyldiacylglycerol and triacylglycerol species) and retrograde endocannabinoid signaling to modulate mitochondrial respiration (phosphatidylcholine, phosphatidylethanolamine and diacylglycerol species) [ 26 ].…”
Section: Lrrk2 Mitochondrial Energy and Glucose/insulin Pathwaysmentioning
confidence: 99%